1969
DOI: 10.3758/bf03210078
|View full text |Cite
|
Sign up to set email alerts
|

Relative olfactory intensity perception as mediated by ratio-range category scale responses

Abstract: METHOD Subjects The Ss were 102 undergraduates, mostly first-year psychology students, 51 male and 51 female, all naive with respect to the psychophysical theory involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1970
1970
1989
1989

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In their experiments, some steps between adjacent stimulus levels appear small enough to challenge the Os' capacity to discriminate successfully one level from another (cf. Gregson, Mitchell, Simmonds, & Wells, 1969). When an experiment is set up in such a way as to allow estimates of perceived magnitude to be controlled by discriminal capacity, Os may sometimes exaggerate the differences among their estimates in order to demonstrate their ability to resolve small differences among the stimuli (Stevens, 1958), whereas at other times, they may not even be able or may not attempt to resolve small differences.…”
Section: Prediction Of the Exponentmentioning
confidence: 99%
“…In their experiments, some steps between adjacent stimulus levels appear small enough to challenge the Os' capacity to discriminate successfully one level from another (cf. Gregson, Mitchell, Simmonds, & Wells, 1969). When an experiment is set up in such a way as to allow estimates of perceived magnitude to be controlled by discriminal capacity, Os may sometimes exaggerate the differences among their estimates in order to demonstrate their ability to resolve small differences among the stimuli (Stevens, 1958), whereas at other times, they may not even be able or may not attempt to resolve small differences.…”
Section: Prediction Of the Exponentmentioning
confidence: 99%
“…111). Gregson et al (1963) noted that a free modulus and a reference unidentified to the judge gave consistently lower magnitude estimates of odor intensity of eugenol than a fixed modulus of 10, corresponding to the same, identified, reference. However, the exponents of the resulting power functions did not differ between the two conditions.…”
Section: Use Of Fixed Versus Free Modulus In Magnitude Estimationmentioning
confidence: 92%
“…While JIohn (1969) found the usual logarithmic relation between category ratings and magnitude estimates of loudness, Sjoeberg (1968aSjoeberg ( , 1968b found linear relations ainnng magnitude scales and category scales of facial expressions when one lype of analysis was performed and curvilinear relations in another study. Gregson, Mitchell, Simmonds, and Wells (1969) found that, when two anchors were given for ratio judgments of odors, the scale acted like a category .i,': Montgomery (1975) summarized studies in which the importance of methodological differences between category rating and magnitude estimation was examined. In one study, the form of a scale obtained by a direct estimation procedure was found to vary with: (a) the range of responses actually used by the subject, and (b) the amount of freedom in choosing a highest number.…”
Section: Relating One Scale To Anothermentioning
confidence: 99%